Vocational Boarding School Curriculum Policy - Sumarna, Asep; Kusmayadi, Andri; Dafik Sahal, Yosep Farhan; Yuliati Zaqiah, Qiqi (STAI Miftahul Ula Nganjuk, 2024)
This study investigates curriculum policies in boarding schools operated by Vocational High Schools (SMK) within the context of Islamic education. The primary aim is to explore how Islamic principles and occupational competencies are integrated into the curriculum. The research employed analysis of policy documents, interviews with stakeholders, and surveys of curriculum implementation across various vocational boarding schools. Findings indicate that the curriculum strategy in SMK boarding schools is established through a comprehensive approach that combines strong Islamic religious instruction with technical and vocational knowledge. The program aims to foster students' spiritual growth while preparing them for the workforce. Islamic religious issues are not only taught theoretically but are also woven into vocational practices, such as business ethics in vocational case studies. Moreover, the study found that flexible curriculum adaptation is essential to meet the demands and local contexts of each vocational boarding school. Active participation from all stakeholders, including teachers, students, parents, and local communities, is crucial for the development and implementation of effective curricula. The study concludes that curricular policies in vocational boarding schools should maintain a balanced approach between religious and vocational education, emphasizing character development. Community involvement, continuous curriculum evaluation, and revision are critical recommendations for enhancing the quality of education in SMK boarding schools.